Cyclophane‐Based Fluorescence Tuning Induced by Hydrostatic Pressure Changes. Issue 11 (26th August 2018) - Sagara, Yoshimitsu; Tamaoki, Nobuyuki; Fukuhara, Gaku
Abstract: In contrast to a standard steady fluorescence intensity increase of a chloroform solution of a linear chromophore unit under high pressure, a fluorescent cyclophane solution shows significant fluorescence quenching under elevated pressure. A pressure‐induced enhancement of the formation of an intramolecular π‐stacked conformation is proposed to be responsible. Abstract : Under pressure : A fluorescent cyclophane solution shows significant fluorescence quenching under elevated pressure. The formation of a pressure‐induced intramolecular π‐stacked conformation is proposed to be responsible.